Underestimating the Real Growth of GDP, Personal Income, and Productivity - Feldstein, Martin (The Journal of economic perspectives, 2017)
Economists have long recognized that changes in the quality of existing goods and services, along with the introduction of new goods and services, can raise grave difficulties in measuring changes in the real output of the economy. But despite the attention to this subject in the professional literature, there remains insufficient understanding of just how imperfect the existing official estimates actually are. After studying the methods used by the US government statistical agencies as well as the extensive previous academic literature on this subject, I have concluded that, despite the various improvements to statistical methods that have been made through the years, the official data understate the changes of real output and productivity. The official measures provide at best a lower bound on the true real growth rate with no indication of the size of the underestimation. In this essay, I briefly review why national income should not be considered a measure of well-being; describe what government statisticians actually do in their attempt to measure improvements in the quality of goods and services; consider the problem of new products and the various attempts by economists to take new products into account in measuring overall price and output changes; and discuss how the mismeasurement of real output and of prices might be taken into account in considering various questions of economic policy.